An extremely rare case of concurrent BRAF V600E mutation driven hairy cell leukemia and melanoma: case report and review of literature - Ghorbani-Aghbolaghia, Amir; Lechpammer, Mirna; Ali, Saba F.; Ku, Nam K.; Dwyre, Denis M.; Rashidi, Hooman H. (Autopsy and Case Reports, 2017)
BRAF protein is a serine/threonine kinase with 766 amino acids. Approximately 15% of human cancers harbor BRAF mutations as well as other BRAF anomalies (amplifications, fusions). Somatic mutations mainly occur in the catalytic kinase domain (CR3), and the predominant mutation is p.V600E which is the substitution of glutamic acid (E) for valine (V) as result of a mutation at codon 600 of the kinase domain. To our knowledge, the vast majority of the cancers have non-germline BRAF mutations. Here we describe a case of a 60-year-old female with a history of hairy cell leukemia (HCL) who presented with aphasia and forgetfulness. A follow-up Brain CT scan showed three distinct brain lesions which were found to be diagnostic of melanoma (confirmed by immunohistochemistry) with no evidence of a concurrent brain involvement by a B-cell neoplasm. Molecular studies confirmed the same BRAF p.V600E mutation in both malignancies (hairy cell leukemia and melanoma). Thereafter the patient was started on BRAF inhibitor treatment and is now symptom-free after one year of follow up. Having two concurrent malignancies with a shared BRAF mutation is extremely rare and makes this an excellent example of a genomic marker-driven treatment in two histologically and immunophenotypically distinct tumors